(untitled) (Development Service Industry Management, 2025)
In the era of globalization and deepening environmental crisis, a new paradigm of competitiveness is being formed, based on the principles of the "green" economy and sustainable development, new factors of competitive advantage are coming to the fore: environmental innovation, corporate responsibility, efficient use of energy and resources, eco-certification of products, and compliance with international standards of sustainable development. The transformation of the competitive paradigm in the context of developing a green economy is practically significant for state policy, enterprise strategic management, and sustainable economic growth. The purpose of the publication is to deepen the theoretical, methodological, and applied principles of the transformation of the competitive paradigm in the context of the development of a green economy. Results. The article examines the essence of the green economy and competitiveness, their modern rethinking in the context of post-industrial development, and global environmental challenges. The key areas of contemporary strategies for competitive advantage are identified: environmental innovation, social responsibility, alignment with ESG standards, and circular business models. The growing role of enterprise environmental flexibility as a factor in long-term sustainability is emphasized, as is the importance of implementing environmental management systems (ISO 14001). Particular attention is paid to state regulation as a factor in the formation of a new competitive environment. The instruments of state influence are revealed, including fiscal incentives for environmental innovations, regulatory standards, green public procurement, and support for eco-technologies. It is noted that in the Ukrainian context, the development of a "green" economy is considered not only an environmental but also a geopolitical need, driven by the European integration course and the need to comply with European standards for sustainable development. The main challenges for domestic businesses are identified: high energy intensity of production, limited access to financing, limited awareness among SMEs of ESG standards, and insufficient coordination between state policy and business needs. Conclusions. The development of the green economy is a catalyst for significant changes in the competitive dynamics of the modern world, where there is not just an adaptation of traditional business models to new requirements, but a fundamental rethinking of the nature of competition. The transformation of the competitive paradigm in the conditions of the green economy involves: the introduction of new criteria for assessing the success of an enterprise; the development of mechanisms for state support for "green" initiatives; the integration of environmental standards into corporate governance; and intersectoral and international cooperation based on sustainable development.